Perceived factors for delayed consultation of cervical cancer among women at a selected hospital in Rwanda: An exploratory qualitative study - Esperance Benemariya; Geldine Chironda; Aimable Nkurunziza; Godfrey Katende; Ruth Sego; Madeleine Mukeshimana (Elsevier, 2018)
Background: Cervical cancer, although a largely preventable disease, is one of the most common cancers found in women living in low and middle-income countries. Cervical cancer management remains a challenge in most developing countries due to the fact that women seek medical care at a later stage. Purpose of the study: The purpose of this study is to explore the perceived factors contributing to delayed consultation for cervical cancer among women at a selected hospital in Rwanda. Methods: The study utilizes an explorative, qualitative design. Twelve (12) women diagnosed with cervical cancer were involved in the study. Four (4) key informants (KI) were also interviewed for the study. A semi-structured interview guide was designed and used to collect the data from both the participants in the FDG and KI. The data was managed and analyzed using Thematic Analysis. Results: Patient, health care providers and health care system factors emerged from the participants' narratives as factors that contributed to the delay in seeking early diagnosis and treatment. The perceived patient-related factors were a lack of knowledge, cultural practices, age related factors, fear of people knowing, and socioeconomic factors. Also, the health care provider delay-related factors were inadequate knowledge, unnecessary treatment, poor communication, and minimizing patients' symptoms, false diagnosis; health care system delay-related factors included an ineffective transfer system and delayed diagnosis. Conclusion: The findings of our study show that patient-related factors and health care system factors were perceived by the women and heath care providers as the contributing factors to the delay of consultation for cervical cancer. These findings should be taken into account during the planning, training of health care providers, measuring quality, and empowering both providers and communities while conducting studies about cervical cancer. The results generated in this research may contribute to the advancement of the cancer diagnosing process in Rwanda. Keywords: Contributing factors, Delayed consultation, Cervical cancer, Rwanda